2021
DOI: 10.1111/jpc.15737
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of mortality in children admitted with SARS‐CoV‐2 infection to a tertiary care hospital in North India

Abstract: Aim To compare the demographic, clinical, laboratory and radiological parameters of patients with different clinical outcomes (death or discharge) and analyse them to find out the potential predictors for mortality in children hospitalised with SARS‐CoV‐2 infection. Methods Retrospective chart review of all patients less than 18 years of age with laboratory‐confirmed SARS‐CoV‐2 infection and requiring hospital admission between 16 April 2020 and 31 October 2020. Results Of 255 children with SARS‐CoV‐2 infectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(22 citation statements)
references
References 26 publications
(72 reference statements)
0
14
0
Order By: Relevance
“…Our results are also in line with a recent systematic review up to May 2021, which also found higher odds of severe disease and death in CYP aged >10 years and underlying comorbidities, especially neurological or cardiac conditions [ 42 ], which is consistent with other published studies [ 11 , 15 , 42 , 43 ]. Notably, however, compared to children who died of other causes in England, previous analyses found that underlying health conditions were not overrepresented in children who died of COVID-19 [ 15 , 44 ], or among survivors and non-survivors in children hospitalised for COVID-19 [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our results are also in line with a recent systematic review up to May 2021, which also found higher odds of severe disease and death in CYP aged >10 years and underlying comorbidities, especially neurological or cardiac conditions [ 42 ], which is consistent with other published studies [ 11 , 15 , 42 , 43 ]. Notably, however, compared to children who died of other causes in England, previous analyses found that underlying health conditions were not overrepresented in children who died of COVID-19 [ 15 , 44 ], or among survivors and non-survivors in children hospitalised for COVID-19 [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…Such a figure is considerably lower than what is reported among hospitalized adult COVID-19 patients in India and abroad [ 12 , 16 , 17 ]. Other Indian reports on the pediatric population, mainly from tertiary care centers, have reported mortality ranging from 3.2% to 11.2% [ 6 , 18 , 19 ]. The present study, being a representative cohort, gives a holistic estimate of poor outcomes across treatment centers and the multiple waves of the pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…Although the role of comorbidities in relation to COVID-19 severity is relatively well understood, non-chronic symptomatic presentations at the time of testing have primarily been studied in relation to biomarkers and prognostic factors 21 , 22 , 23 rather than examining the association initial symptoms and later hospitalization or death. Our study demonstrates some of the first population-derived results on symptoms in a cohort of SARS-CoV-2 positive individuals, regardless of hospitalization status.…”
Section: Discussionmentioning
confidence: 99%